EVALUASI KEBIJAKAN PERLINDUNGAN SOSIAL BAGI PEKERJA MIGRAN INDONESIA (PMI) YANG DIDEPORTASI DARI MALAYSIA DI KOTA TANJUNG PINANG - Ferdi Septianda (Universitas Muhammadiyah Lampung, 2023)
ABSTRACTThe problem of the deportation of Indonesian Migrant Workers from Malaysia in Tanjung pinang City is a complex problem. Thus, the Government presents a social protection policy that is based on strong legal rules and applies before work, during work, and after work. The purpose of this study is to find out whether the social protection policies implemented by relevant stakeholders have been implemented properly or vice versa. Another objective is to obtain data, information and programs related to social protection policies. This study uses a qualitative method with a descriptive research type. In order to obtain primary data, in-depth interviews were conducted with informants. Secondary data is obtained through literature study, namely searching for data through journals, articles, and internet sources. The results of the discussion and research referring to William N Dunn's policy evaluation theory show that social protection policies have worked well in terms of effectiveness, efficiency, equity, responsiveness and distribution. Five of the six indicators are met thanks to the commitment and good cooperation of each stakeholder. However, in terms of the adequacy indicator, the budget spent is not sufficient. There must be an increase in the budget from the central government so that stakeholders are more flexible and creative in implementing and making programs so that social protection policies will improve in the future.Â Keyword: Policy Evaluation, Social Protection, Deportation